2014
DOI: 10.1002/etc.2684
|View full text |Cite
|
Sign up to set email alerts
|

Acute sensitivity of white sturgeon (Acipenser transmontanus) and rainbow trout (Oncorhynchus mykiss) to copper, cadmium, or zinc in water‐only laboratory exposures

Abstract: The acute toxicity of cadmium, copper, and zinc to white sturgeon (Acipenser transmontanus) and rainbow trout (Oncorhynchus mykiss) were determined for 7 developmental life stages in flow-through water-only exposures. Metal toxicity varied by species and by life stage. Rainbow trout were more sensitive to cadmium than white sturgeon across all life stages, with median effect concentrations (hardness-normalized EC50s) ranging from 1.47 µg Cd/L to 2.62 µg Cd/L with sensitivity remaining consistent during later s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 37 publications
5
57
0
Order By: Relevance
“…This sensitivity to Cu was reaffirmed in the present study with effect concentrations for mortality and loss of equilibrium and immobilization similar to previously reported values (Calfee et al ), with the exception of the 4‐d EC50 for loss of equilibrium and immobilization. In the present study, EC50s for this endpoint ranged from 8.71 to 8.88 μg Cu/L for 1‐ to 35‐dph white sturgeon larvae, whereas Calfee et al () reported values of 2.67 to 6.31 μg Cu/L. In a recent study with Chinese sturgeon ( Acipenser sinensis ), similar swimming aberrations indicative of a loss of equilibrium, such as fish swimming in corkscrews and losing their balance, were observed after 4 to 6 h of exposure to high concentrations of Cu (up to 110 μg/L; Feng et al ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This sensitivity to Cu was reaffirmed in the present study with effect concentrations for mortality and loss of equilibrium and immobilization similar to previously reported values (Calfee et al ), with the exception of the 4‐d EC50 for loss of equilibrium and immobilization. In the present study, EC50s for this endpoint ranged from 8.71 to 8.88 μg Cu/L for 1‐ to 35‐dph white sturgeon larvae, whereas Calfee et al () reported values of 2.67 to 6.31 μg Cu/L. In a recent study with Chinese sturgeon ( Acipenser sinensis ), similar swimming aberrations indicative of a loss of equilibrium, such as fish swimming in corkscrews and losing their balance, were observed after 4 to 6 h of exposure to high concentrations of Cu (up to 110 μg/L; Feng et al ).…”
Section: Discussionsupporting
confidence: 93%
“…White sturgeon larvae were among the most sensitive to Cu exposure among aquatic organisms based on species sensitivity distributions of previously reported values for other organisms (Vardy et al ; Little et al ; Calfee et al ; Wang et al ). This sensitivity to Cu was reaffirmed in the present study with effect concentrations for mortality and loss of equilibrium and immobilization similar to previously reported values (Calfee et al ), with the exception of the 4‐d EC50 for loss of equilibrium and immobilization. In the present study, EC50s for this endpoint ranged from 8.71 to 8.88 μg Cu/L for 1‐ to 35‐dph white sturgeon larvae, whereas Calfee et al () reported values of 2.67 to 6.31 μg Cu/L.…”
Section: Discussionmentioning
confidence: 96%
“…White sturgeon free embryos hide in the interstitial spaces of the substrate at the bottom of the river and are observed hiding under provided refugia in laboratory studies (Figure 3C). During this life stage, sturgeon are approximately 1 to 7 dph, and concentrations that are lethal to 50% of the experimental population in 96 h (96‐h LC50s) range for Cu from 5 to >16 μg/L (Calfee et al 2014; Wang et al 2014) (Table 1; Note: this and numbers listed from here are BLM adjusted to USEPA [2002] moderately hard standard water for ease in comparison among studies). However, an effect concentration that includes mortality, loss of equilibrium, and immobility in its calculation, for the same life stage, is the most sensitive acute endpoint and a more realistic interpretation of Cu effects.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, adverse behavioral responses were evident with early onset during the first few days of acute and chronic exposures to copper and became progressively more severe over exposure duration and concentration 7,8,9 . The magnitude and timing of the onset of these behavioral responses are likely sufficient to limit long-term survival and thus are of concern given the implications for recruitment failure 10 .…”
Section: Introductionmentioning
confidence: 88%